2020
DOI: 10.3892/ol.2020.11392
|View full text |Cite
|
Sign up to set email alerts
|

Serum melatonin is inversely associated with matrix metalloproteinase‑9 in oral squamous cell carcinoma

Abstract: Matrix-metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) expression levels have been demonstrated to have prognostic value in oral squamous cell carcinoma (OSCC). The present study hypothesized that melatonin, a small lipophilic molecule primarily secreted by the pineal gland, may be able to regulate MMP activity in OSCC progression. This study aimed to investigate the associations between melatonin, MMPs, TIMPs and the histopathological characteristics of patients with OSCC. A total of 40 men with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…In addition, they reported that the serum melatonin levels were negatively correlated with matrix metalloproteinase-9 (MMP 9). Low levels of serum melatonin and high levels of serum MMP-9 were correlated with larger tumor sizes and higher invasiveness and lymph node metastasis [27]. However, in our study, we did not observe a correlation between serum melatonin and tumor size or lymph node metastasis.…”
Section: Discussioncontrasting
confidence: 95%
“…In addition, they reported that the serum melatonin levels were negatively correlated with matrix metalloproteinase-9 (MMP 9). Low levels of serum melatonin and high levels of serum MMP-9 were correlated with larger tumor sizes and higher invasiveness and lymph node metastasis [27]. However, in our study, we did not observe a correlation between serum melatonin and tumor size or lymph node metastasis.…”
Section: Discussioncontrasting
confidence: 95%
“…Bleeding events like hemoptysis or pulmonar y haemorrhage are common adverse events associated with bevacizumab and may lead to fatal outcome. Tumour cavitation was associated with an increased risk for bleeding in some studies, and other studies show an increased risk associated with central tumour location, squamous histology and invasion of major blood vessels [13,[17][18][19][20][21]. In our study, 2 patients presented hemoptysis, in one patient hemoptysis was grade 1, and in another patient grade 2, and required administration of hemostatic therapy.…”
Section: Resultssupporting
confidence: 53%
“…OSCC was generally asymptomatic in the early stages, which can lead to late diagnosis, extensive lesions, and potential metastases, while lymph node metastases were widely recognized as a major cause of poor survival ( Gharat et al, 2016 ; Bray et al, 2018 ; Velmurugan et al, 2020 ). The 5-year survival for OSCC has been reported approximately 50% ( Warnakulasuriya, 2009 ; Taghavi and Yazdi, 2015 ; Stanciu et al, 2020 ). Despite intervention with advanced treatment regimens like chemoradiotherapy, surgery, EGFR (epidermal growth factor receptor) inhibitors and COX-2 inhibitors, and photodynamic therapy, survival rate of OSCC has not improved significantly in recent decades ( Rhodus et al, 2014 ; Chi et al, 2015 ; Gupta et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%